Caring for Clients and Families With Anxiety - Noriko Yamamoto-Mitani; Maiko Noguchi-Watanabe; Hiroki Fukahori (SAGE Publishing, 2016)
This study elucidated Japanese home care nurses' experiences of supporting clients and families with anxiety. We interviewed 10 registered nurses working in home care agencies and analyzed the data using grounded theory to derive categories pertaining to the nurses' experiences of providing care. We conceptualized nurses' approaches to caring for anxiety into three categories: First, they attempted to reach out for anxiety even when the client/family did not make it explicit; second, they tried to alter the outlook of the situation; and third, they created comfort in the lives of the client/family. The conceptualizations of nurses' strategies to alleviate client/family anxiety may reflect Japanese/Eastern cultural characteristics in communication and their view of the person and social care system, but these conceptualizations may also inform the practice of Western nurses by increasing awareness of skills they may also have and use.